2011
DOI: 10.1038/ejhg.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cavernous malformations: from molecular pathogenesis to genetic counselling and clinical management

Abstract: Cerebral cavernous (or capillary-venous) malformations (CCM) have a prevalence of about 0.1-0.5% in the general population. Genes mutated in CCM encode proteins that modulate junction formation between vascular endothelial cells. Mutations lead to the development of abnormal vascular structures. In this article, we review the clinical features, molecular and genetic basis of the disease, and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 83 publications
0
81
0
1
Order By: Relevance
“…9 Based on the assumption of a potentially increased hemorrhage risk under long-term antithrombotic therapy, current recommendations advise against the use of such medication in the presence of one or more CCMs. 2,10 However, no systematic studies exist to support this hypothesis.…”
mentioning
confidence: 99%
“…9 Based on the assumption of a potentially increased hemorrhage risk under long-term antithrombotic therapy, current recommendations advise against the use of such medication in the presence of one or more CCMs. 2,10 However, no systematic studies exist to support this hypothesis.…”
mentioning
confidence: 99%
“…It has been proposed that haploinsufficiency manifests through various ways in CCM, such as inadequate protein production for endothelial junction formation, causing the pseudovascular formation characteristic of CCM. 12 Though this can be seen as an adequate explanation for disease mechanism, it would not fit the presentation of our patient as haploinsufficiency would indicate disease progression since birth, which was not the case here.…”
Section: Haploinsufficiencymentioning
confidence: 65%
“…The prevalence of CM in the general population ranges from 0.16 % to 0.5 % (Del Curling et al 1991;Baumann et al 2006;Morris et al 2009;Krisht et al 2010;Kivelev 2011;Cavalcanti et al 2012;Haasdijk et al 2012;Al-Holou et al 2012). The incidence of cavernomas is equal in both genders (Del Curling et al 1991;Kondziolka et al 1995;Kivelev 2012;Gross et al 2011;Al-Holou et al 2012), and it seems to be increasing with the wide availability of MRI (Kondziolka et al 1995;Aiba et al 1995;Washington et al 2010;Dalyai et al 2011;Al-Holou et al 2012), and imaging prevalence of cavernomas had been noted to be increasing with advancing age (Al-Holou et al 2012;Robinson et al 1991).…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Linkage studies have shown that a CCM1 mutation is involved in up to 40 % of familial CCMs, and nearly half of those patients will have neurological symptoms before 25 years of age (Yadla et al 2010). It has 20 exons of which 16 encodes Krev interaction trapped 1 (Krit1), a 736-amino-acid microtubule-associated protein containing 4 ankyrin domains, one at C terminal (FERM) (i.e., band 4.1, ezrin, radixin, moesin), and three at N-terminal NPXY (Asn-Pro-XTyr) motifs (Cavalcanti et al 2012;Haasdijk et al 2012).…”
Section: Genetic Of Cavernomamentioning
confidence: 99%
See 1 more Smart Citation